Ligand-Assisted Formation of Graphene/Quantum Dot Monolayers with Improved Morphological and Electrical Properties - Aleksandr P. Litvin; Anton A. Babaev; Peter S. Parfenov; Aliaksei Dubavik; Sergei A. Cherevkov; Mikhail A. Baranov; Kirill V. Bogdanov; Ivan A. Reznik; Pavel O. Ilin; Xiaoyu Zhang; Finn Purcell-Milton; Yurii K. Gun’ko; et al. (Nanomaterials, 2020)
Hybrid nanomaterials based on graphene and PbS quantum dots (QDs) have demonstrated promising applications in optoelectronics. However, the formation of high-quality large-area hybrid films remains technologically challenging. Here, we demonstrate that ligand-assisted self-organization of covalently bonded PbS QDs and reduced graphene oxide (rGO) can be utilized for the formation of highly uniform monolayers. After the post-deposition ligand exchange, these films demonstrated high conductivity and photoresponse. The obtained films demonstrate a remarkable improvement in morphology and charge transport compared to those obtained by the spin-coating method. It is expected that these materials might find a range of applications in photovoltaics and optoelectronics.